A Multifloor Path-Loss Model for 433 MHz LoRa-WAN in Concrete Buildings - Phokharatkul P. (2023)
LPWAN (low power wide-Area network) for smart building applications will benefit positioning, energy management system, parking and so on. This paper proposes a propagation model for LPWAN 433 MHz in two different concrete buildings, 5 story laboratory and parking buildings. The path loss model in terms of RSSI (received signal strength indicator) calculation uses empirical measurement data. The path-loss exponent for LoS propagation of the proposed prediction model is found to be 2.03 and 1.99. Again, for the NLoS propagation links, the floor attenuation factors (FAF) of 1 to 5 floors are found to be 6.0, 10.8, 13.9, 17.0 and 9.8, 14.0, 17.2, 21.5 for the first and the second buildings respectively